Method of heating of the separated parts of launch vehicle during the atmospheric phase of the descent trajectory. (April 2019) - Trushlyakov, V.; Panichkin, A.; Lempert, D.; Shatrov, Ya.; Davydovich, D.
Abstract: A new method for heating the structure of separated parts (like aft interstage, made of a polymer composite material) of launch vehicle up to its ignition temperature is developed, including the physico-mathematical model of heat- and mass transfer based on Navier-Stokes equations and a simplified methodology for implementing the difference scheme for numerical solution of these equations. The source of necessary amount of heat release for heating aft interstage (AIS) up to the ignition temperature is the combustion heat of an energetic material (EM) installed directly inside AIS. Energetic materials can be substances that emit heat during combustion. An example of energetic material can be pyrotechnic compositions, rocket fuels, etc. It is assumed that as soon the temperature of the AIS reaches its ignition temperature, the AIS begins to burn in oncoming airflow with the release of the heat amount enough for the rest mass of the AIS ignition. As an example of the implementation of the method, the results of the estimated temperatures of the AIS structures (made of CFRP) at the EM (oxygen + propane) burning are represented for the fixed point of the flight time at the atmospheric phase of the descent trajectory. The AIS of the launch vehicle "Soyuz" has been considered using two codes: ANSYS FLUENT and the developed code for the numerical solution the difference scheme of the Navier-Stokes equations. The results obtained with the both of these codes are in an acceptable error zone for calculations of the conjugate heat transfer, and the dispersion between these two methods is less than 20%. Highlights: The thermal load parameters on the aft interstage example in the descent trajectory. Estimating the thermal load based on a centered-set and the distributed model. Using two methods for the numerical solution of Navier – Stokes equations.